The Students’ Competence in English Grammar and Writing: A Corelative Study at the Second grade Students of MTs. Al-Muini, Sesela Gunungsari - Terasne (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Abstrak: Penelitian ini dimaksudkan untuk menemukan hubungan antara kompetensi tata bahasa siswa dan keterampilan menulis mereka. Sampel yang dipilih adalah siswa kelas II MTs. Al-Muini Sesela terdiri dari 35 siswa. Siswa diberikan 25 soal berbentuk pilihan ganda pada tes kompetensi tata bahasa dan diminta menulis minimal 100 kata tentang pengalamannya dalam bentuk paragraf pada tes keterampilan menulis. Prosedur pengumpulan data menggunakan teknik tes dengan menggunakan rumus: rxy=X/(Xy2)x(Xy2). Temuan yang diperoleh adalah: 1) rata-rata siswa memperoleh nilai yang cukup baik dalam tes kompetensi tata bahasa. Hal ini terlihat dari hasil rata-rata nilai siswa sebesar 6,76. 2) rata-rata siswa memperoleh nilai cukup baik dalam tes keterampilan menulis. Hal ini terlihat dari rata-rata nilai siswa sebesar 6,74. 3) Terdapat korelasi antara kompetensi tata bahasa siswa dengan keterampilan menulisnya yang dapat dilihat dari nilai “r” dengan N = 35 (r= 0,823) lebih besar dari nilai “r” pada tabel ( r= 0,334) pada taraf signifikansi 5% dan (r= 0,430) pada taraf signifikansi 1%. Oleh karena itu, hasil penelitian menunjukkan bahwa kompetensi tata bahasa mempunyai peran yang tinggi dalam keterampilan menulis. Jelas bahwa hipotesis alternatif (Ha) yang menyatakan “ada korelasi antara kompetensi tata bahasa siswa dan keterampilan menulis mereka diterima. Kata Kunci: siswa, kompetensi, tata bahasa inggris, keterampilan menulis Abstract: This study is intended to discover the correlation between students’ grammar competence and their writing skill. The samples chose was the second grade students of MTs. Al-Muini Sesela consists 35 students. The students were given 25 questions in the form of multiple choice types on grammar competence test and they were asked to write at least 100 words about their experience in the form of paragraph on writing skill test. The procedure of collecting data was testing technique by using formula: rxy= /(Xy2)x(Xy2). The result findings were: 1) the students’ average gets fairly good score in grammar competence test. It can be seen from the result of mean of the students’ score that was 6.76. 2) the students’ average get fairly good score in their writing skill test. It can be seen from the mean of the students’ score that was 6.74. 3) There is a correlation between the students’ grammar competence and their writing skill which can be observed from the value of “r” with N = 35 (r= 0.823) that was greater than the value of “r” at the table (r= 0.334) at the level of significance 5% and (r= 0.430) at the level of significance 1%. Therefore, the result shows that grammar competence has a high role in writing skill. It is clear that the Alternative hypothesis (Ha) which says “there is a correlation between students’ grammar competence and their writing skill was accepted. Keywords: students, competence , english grammar, writing skill